PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR SUB SEKTOR ELEKTRONIKA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019 – 2021 - Joana Rosie Shabatiny Degely; Salman Al Farisi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to analyze the influence of capital structure, company size and profitability on company value in electronics sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The purposive sampling method is used to select a sample of companies that meet certain criteria. Secondary data was obtained from audited company annual reports, and analysis was carried out using panel data regression. The research results show that capital structure, company size, and profitability have a significant influence on company value. Apart from that, this study also recommends adding independent variables and extending the research period for more complete results and better generalization. These findings provide important insights for investors, company management and researchers to understand the factors that influence company value in the context of the electronics industry in Indonesia.